Vapor compression refrigeration system with air and water cooled condenser: Analysis of thermodynamic behavior and energy efficiency ratio - Setiyo, Muji; Rusdjijati, Retno; Habibi, Ilham; Rochman, Muhamad Latifur; Purnomo, Bagiyo Condro; Pertiwi, Fungky Dyan; Waluyo, Budi; Ismail, Rifky; Kolakoti, Aditya (Universitas Negeri Padang, 2024)
This study presents the analysis of thermodynamic behavior and energy efficiency of a vapor compression refrigeration system with two types of condensers: air-cooled (ACC) and water-cooled (WCC). The main objective is to assess the system performance by comparing the Coefficient of Performance (COP) and Energy Efficiency Ratio (EER) under both condenser configurations. During a 12-hour test period, data on refrigerant pressure, temperature, and electrical energy consumption were collected and analyzed. The results show that the WCC system outperforms the ACC system, showing a 5.7% increase in heat rejection and a 4.2% increase in cooling capacity. In addition, the WCC system exhibits a lower compressor duty cycle and consumes less electrical energy, resulting in a higher total EER of 5.658 compared to ACC of 1.945. These findings suggest that integrating a water-cooled condenser into a refrigeration system can significantly improve energy efficiency and reduce operating costs, making it a viable option for commercial applications in tropical regions.